2015
DOI: 10.1371/journal.pone.0133122
|View full text |Cite
|
Sign up to set email alerts
|

Matching Fishers’ Knowledge and Landing Data to Overcome Data Missing in Small-Scale Fisheries

Abstract: BackgroundIn small-scale fishery, information provided by fishers has been useful to complement current and past lack of knowledge on species and environment.MethodologyThrough interviews, 82 fishers from the largest fishing communities on the north and south borders of a Brazilian northeastern coastal state provided estimates of the catch per unit effort (CPUE) and rank of species abundance of their main target fishes for three time points: current year (2013 at the time of the research), 10, and 20 years pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 27 publications
(35 reference statements)
4
43
0
1
Order By: Relevance
“…This agrees with previous studies indicating decreases in catches over time and even local extinctions, according to fishers' knowledge [18,22,31,35,39,59,67]. Nevertheless, a recent study has not evidenced a decline in the biomass of fish caught in the northeastern Brazilian coast during the last 10 years [21]. The observed decrease in the biomass of fish caught also agree with concerns of coastal fishers regarding intense fishing pressure by large scale fishers [3,15,65].…”
Section: Temporal Trends In Catch Abundance and Compositionsupporting
confidence: 91%
See 2 more Smart Citations
“…This agrees with previous studies indicating decreases in catches over time and even local extinctions, according to fishers' knowledge [18,22,31,35,39,59,67]. Nevertheless, a recent study has not evidenced a decline in the biomass of fish caught in the northeastern Brazilian coast during the last 10 years [21]. The observed decrease in the biomass of fish caught also agree with concerns of coastal fishers regarding intense fishing pressure by large scale fishers [3,15,65].…”
Section: Temporal Trends In Catch Abundance and Compositionsupporting
confidence: 91%
“…Recent studies have successfully applied fishers' knowledge to investigate temporal trends in abundance of fishing resources and changes in ecological conditions in a range of freshwater and coastal Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/marpol ecosystems [18,22,35,39,61]. Nevertheless, most of these studies address particular fish species more susceptible to fishing pressure, such as reef fish or sharks [31,59], while fewer studies investigate temporal changes in the amount and composition of fish catches by comparing distinct data-bases, such as governmental landing statistics and fishers' knowledge [21]. Information on temporal trends in fish catches are required to support management interventions and policy measures better suited to the needs and concerns of Brazilian small-scale coastal fishers [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, their actual conservation status might have been unknown to researchers, fisheries managers, and younger fishers before such species were first assessed. This seems to be the case, for example, for C. maculata; in data collected from fishers (see Damasio et al 2015), elderly fishers reported high catches of triggerfishes prior to 2003 and the complete disappearance of current landings. However, fishers used just common names (cangulo) and grouped together several species such as Bali stes vetula, B. capriscus, and Cantherhines macrocerus.…”
Section: Notes On Geographic Distributionmentioning
confidence: 96%
“…In the conservation status may not represent historical declines. In Rio Grande do Norte, fishing activities are considerably unregulated, unreported, and to some extent also illegal (Ross et al 2015;Damasio et al 2015;Bevilacqua et al 2016). Some fisheries and target species are poorly assessed or not assessed at all, and the presence, abundance, and availability for fisheries of some species might be misreported.…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%